ENHANCING MASTERY OF PRACTICAL SKILLS IN STUDENTS OF VOCATIONAL AND TECHNICAL EDUCATION THROUGH ACTIVITY BASED - Odo, M.I.; Adenle, S.O.; OKWORI, R.O. (Journal of Technical Education and Training, 2012)
The study seeks to understand the issues and challenges related to the implementations of activity-based instructions on vocational and technical education student in Nigeria. A survey was carried out involving vocational and technical education teachers in all six government owned technical colleges in Lagos State of Nigeria. A total of 150 teachers were selected randomly as respondents for the study. A four point scale items were designed to elicit information from the respondents. The findings of the study indicated that the techniques and the strategies adopted by the teachers of vocational education include: demonstration, field trips, projects, experiments and assignments. Various methods to evaluate students outcome include: process-product through systematic observation. It was evident from the study that constantly focusing on activity to make learning fun can actually hamper those students who make good progress without it. Based on the findings the researcher therefore concluded that good vocational and technical education teachers require the right attitude, have years of professional and practical skills and entrepreneurial experience at the workshop floor of industry and good background knowledge of engineering design.